2023
DOI: 10.1039/d2ta09797d
|View full text |Cite
|
Sign up to set email alerts
|

Studying the droplet sliding velocity and charge transfer at a liquid–solid interface

Abstract: The contact electrification between liquid and solid has attracted widespread attention from the field of energy, physics and chemistry, but its basic mechanism still remains unclear, especially for the charge...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…[29] The formation of an electric double layer and the charge shielding effect caused by ions at the liquid-solid interface have been reported. [30] Specifically, during the initial contact, electron transfer occurs between the solution and the FEP, resulting in a negatively charged FEP surface. Subsequently, cations in the solution are moved to the negatively charged FEP surface, forming an electric double layer.…”
Section: Liquid-solid Electrification Mechanism Of Sucrose Solutionmentioning
confidence: 99%
“…[29] The formation of an electric double layer and the charge shielding effect caused by ions at the liquid-solid interface have been reported. [30] Specifically, during the initial contact, electron transfer occurs between the solution and the FEP, resulting in a negatively charged FEP surface. Subsequently, cations in the solution are moved to the negatively charged FEP surface, forming an electric double layer.…”
Section: Liquid-solid Electrification Mechanism Of Sucrose Solutionmentioning
confidence: 99%
“…The droplet TENG converts the kinetic energy of the droplet into electricity by contact electrification effect and proper circuit connection. There were two mainstream views on the source of contact electrification between solids and liquids: one is based on the ion transfer mechanism of the double electron layer, and the other is based on the electron transfer mechanism of contact electrification. Recent studies have found that both ion transfer and electron transfer occur simultaneously during the process of contact electrification between solids and liquids and electron transfer plays a dominant role in the contact electrification process between deionized water and PTFE. Therefore, in this paper, we mainly consider electron transfer as the dominant factor in contact electrification. A droplet after L-DTENG working was collected using a Faraday cup, the voltage of Faraday cup was measured during this process (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Past research data has indicated that the introduction of ions may inhibit electron transfer, implying a competitive relationship between electrons and ions. [ 15a,16 ] Therefore, there might be mutual influences between electron transfer and ion absorption. When the ion concentration becomes excessively high, the output performance of D‐TENG may decline with the increase in ion concentration.…”
Section: Resultsmentioning
confidence: 99%